The Viability of Local Ram Semen in Tris Buffer With Three Different Egg Yolks - Nalley, WMM; Arifiantini, RI (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Egg yolk consisted of lecithin and phospholipids are one of the most commonly used components that will protect spermatozoa against cold shock during cooling and freezing. The aim of this study was to evaluate the effect of different hen egg yolk on Tris extender on the freezability of local ram semen. Semen from six sexually matured local rams was collected weekly using artificial vagina. Collected semen was evaluated macroscopically and microscopically and extended using tris extender consisted of 20% (v/v) regular egg yolk (TRCEY), native egg yolk (TNCEY), omega-3 hen egg yolk (TOEY) and 6% (v/v) glycerol. Those were packed in 0.25 ml straws, equilibrated at 5oC for 3 hours, frozen and stored in nitrogen tank for 24 hours, and thawed at 37oC for 30 second. The result of the experiment showed that there were no significant differences on the sperm motility and the number of living sperm. Percentage of plasma membrane intact in TOEY (60.3%) was significantly higher compared to TREY (56.9%) and TNEY (55.6%). In conclusion, the addition of omega 3 egg yolk in Tris extender protects plasma membrane better than the regular or native hen egg yolk. (Animal Production 13 (1):39-44 (2011) Key Words: ram semen, egg yolk, frozen semen